Comparative Performance of Ante-Mortem Diagnostic Assays for the Identification of Mycobacterium bovis-Infected Domestic Dogs (Canis lupus familiaris) - Conor O’Halloran; Paul Burr; Danielle A. Gunn-Moore; Jayne C. Hope (Pathogens)
The domestic dog (Canis lupus familiaris) is a competent host for Mycobacterium (M.) bovis infection but no ante mortem diagnostic tests have been fully validated for this species. The aim of this study was to compare the performance of ante mortem diagnostic tests across samples collected from dogs considered to be at a high or low risk of sub-clinical M. bovis infection. We previously tested a total of 164 dogs at a high risk of infection and here test 42 dogs at a low risk of infection and 77 presumed uninfected dogs with a combination of cell-based and/or serological diagnostic assays previously described for use in non-canid species. The interferon-gamma release assay (IGRA) using peripheral blood mononuclear cells (PBMCs) identified the highest number of test-positive animals (85, 52%), with a suggested specificity of 97.3%, whilst a whole-blood IGRA was found to be unreliable. The production of antigen-specific tumour necrosis factor-alpha (TNF-α) by PBMC in response to a cocktail of ESAT-6 and CFP-10 peptides correlated very strongly with the overall IGRA results, suggesting future diagnostic potential. All three serological assays employed in this study (Idexx M. bovis Ab ELISA, [Idexx Laboratories, Westbrook, ME, USA], DPP VetTB lateral flow assay [Chembio, Medford, NY, USA], and comparative PPD ELISA [in-house]) identified seropositive dogs but, overall, the test-positive rate for the serological assays was only one third that of the cellular-based assays. Circulating serum cytokine concentrations of interferon gamma and TNF-α were not statistically different between the high- and low-risk groups of dogs. While many dogs in the high-risk group had serum biochemical abnormalities, these did not correlate with the findings from the diagnostic TB tests. This study demonstrates, for the first time, the utility of two cellular and three serological assays for detecting sub-clinical M. bovis infections of dogs. Whilst the data suggest a high test specificity for all assays evaluated, further work is needed to validate the sensitivity and specificity of individual or combinations of tests using sufficient numbers of dogs of a known infection status.